2020
DOI: 10.3389/fcimb.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Proteins and Gene Expression Regulation in Trypanosoma cruzi

Abstract: The regulation of gene expression in trypanosomatids occurs mainly at the post-transcriptional level. In the case of Trypanosoma cruzi, the characterization of messenger ribonucleoprotein (mRNP) particles has allowed the identification of several classes of RNA binding proteins (RBPs), as well as non-canonical RBPs, associated with mRNA molecules. The protein composition of the mRNPs as well as the localization and functionality of the mRNAs depend on their associated proteins. mRNPs can also be organized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 104 publications
1
30
0
1
Order By: Relevance
“…The presence of specific RNA binding proteins could then direct the mRNAs for storage or degradation (Hentze, Castello, Schwarzl, & Preiss, 2018). In fact, several RNA binding proteins have been shown to control the fate of the different mRNAs in T. cruzi (Romagnoli, Holetz, Alves, & Goldenberg, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of specific RNA binding proteins could then direct the mRNAs for storage or degradation (Hentze, Castello, Schwarzl, & Preiss, 2018). In fact, several RNA binding proteins have been shown to control the fate of the different mRNAs in T. cruzi (Romagnoli, Holetz, Alves, & Goldenberg, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments comparing the dynamics of association of TcZC3H12 with its target mRNAs and RNP granules during epimastigote growth and differentiation would provide further evidence for the role of this RBP. Although the mechanisms behind the formation of these cytoplasmic RNP granules as well as their function are not yet fully understood, several studies have showed that, both in T. brucei and T. cruzi, these granules are formed in response to nutritional stress and contain proteins homologous to those present in P bodies and stress granules from metazoan organisms (Cassola et al, 2007;Holetz et al, 2007Holetz et al, , 2010Romagnoli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose that the 241 nt repeat could serve as a cis-regulatory element on mRNA, playing a role in the posttranscriptional regulation of surface proteins of T. cruzi . UTR segments are involved in gene expression regulation, regulating mRNA transcription to mRNA decay [ 38 ] and in the interaction of mRNA with other RNA molecules [ 39 ]. Diverse elements in the 3′ UTR region have been described to have cis-regulatory functions in gene expression [ 40 , 41 ] not only in later divergent eukaryotes but also in trypanosomatids [ 10 , 20 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%